2007
DOI: 10.1038/sj.npp.1301570
|View full text |Cite
|
Sign up to set email alerts
|

Induction of c-Fos and ΔFosB Immunoreactivity in Rat Brain by Vagal Nerve Stimulation

Abstract: Vagus nerve stimulation (VNS) is used as therapy for treatment-resistant depression or epilepsy. This study used immunohistochemistry for biomarkers of short-term (c-Fos) and long-term (DFosB) neuronal activation to map regions in brain that are activated by acute (2 h) or chronic (3 weeks) VNS in conscious Sprague-Dawley rats. Electrodes (Cyberonics Inc.) were implanted on the left vagus nerve and 1 week after surgery, stimulation began using parameters employed clinically (one burst of 20 Hz, 250 ms pulse wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 77 publications
14
129
3
3
Order By: Relevance
“…Immunohistochemical studies demonstrate that hypoxia stimulates multiple types of neurons in numerous brain regions including both the noradrenergic LC and serotonergic raphe nuclei (Erickson and Millhorn, 1994;Teppema et al, 1997;Bodineau and Larnicol, 2001). In contrast, vagal modulation predominately activates LC cells that project to hypoglossal motoneurons (Naritoku et al, 1995;Cunningham et al, 2008). Therefore, we hypothesize that intermittent hypoxia recruits both serotonergic and noradrenergic mechanisms that cause both phrenic and hypoglossal LTF, whereas vagusmediated LTF specifically activates a noradrenergic pathway that only causes plasticity in hypoglossal motoneurons.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Immunohistochemical studies demonstrate that hypoxia stimulates multiple types of neurons in numerous brain regions including both the noradrenergic LC and serotonergic raphe nuclei (Erickson and Millhorn, 1994;Teppema et al, 1997;Bodineau and Larnicol, 2001). In contrast, vagal modulation predominately activates LC cells that project to hypoglossal motoneurons (Naritoku et al, 1995;Cunningham et al, 2008). Therefore, we hypothesize that intermittent hypoxia recruits both serotonergic and noradrenergic mechanisms that cause both phrenic and hypoglossal LTF, whereas vagusmediated LTF specifically activates a noradrenergic pathway that only causes plasticity in hypoglossal motoneurons.…”
Section: Discussionmentioning
confidence: 87%
“…Anatomical tracing studies demonstrate that vagal afferents project to the nucleus of the solitary tract (NTS), which in turn innervates LC neurons (Cedarbaum and Aghajanian, 1978;Clavier, 1978;Kalia and Sullivan, 1982;Berthoud and Neuhuber, 2000). Importantly, vagal nerve modulation increases c-Fos activation of noradrenergic LC cells (Naritoku et al, 1995;Cunningham et al, 2008), which in turn project directly to hypoglossal motoneurons (Aldes et al, 1992). We hypothesize that obstructive apneas modulate vagal afferents, which indirectly (i.e., via NTS) activate LC neurons to increase noradrenaline release onto hypoglossal motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent studies have also shown VNS increase c-fos expression, which acutely activates the locus ceruleus and chronically activates the NTS, paraventricular nucleus of the hypothalamus, parabrachial nucleus, ventral bed nucleus of the stria terminalis, cingulated nucleus, and dorsal raphe nucleus. 22 VNS may also increase GABA release, which stimulates the vagus nerve and decreases seizure activity. These effects likely form the basic mechanism(s) by which VNS reduce seizure activity.…”
Section: Question 1: How Do Vagus Nerve Stimulators Work and What Armentioning
confidence: 99%
“…43 The observation of increased c-fos expression in response to acute and chronic VNS in rats also supports the role of locus coeruleus activation in the acute phase, along with long-term activation of the NTS, paraventricular nucleus of the hypothalamus, parabrachial nucleus, ventral bed nucleus of the stria terminalis, cingulate cortex, and dorsal raphe nucleus. 44 A marginal decrease in CSF aspartate with 3 months of VNS is also of interest, given the excitatory properties of aspartate. 41 Indeed, decreased levels of excitatory neurotransmitters may be one factor in the mechanisms underlying improved seizure control.…”
Section: Rationale and Proposed Mechanisms Of Vns In Epilepsy Controlmentioning
confidence: 99%